2016
DOI: 10.3126/jfstn.v9i0.12579
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Microbial Consortium in Sri Lankan Buffalo Milk Curd and their growth in the Presence of Prebiotics

Abstract: The production and consumption of traditionally fermented buffalo milk curd provides many economical and food security benefi ts to both producers and consumers in the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…bulgaricus and L. casei subsp. casei, Streptococcus thermophilus and S. lactis, S. diacetylactis, S. cremoris under controlled fermentation [75]. Buffalo milk has high total solids content (16.3 to 18.4%); protein (3.8 to 4.5%), fat (6.6 to 8.8%), lactose (4.5 to 5.2%), and casein (3.0 to 3.2%) compared with cow's milk [76] and produces a firmer curd that is a bio-therapeutic agent with a long history of use in traditional medicine.…”
Section: Dairymentioning
confidence: 99%
“…bulgaricus and L. casei subsp. casei, Streptococcus thermophilus and S. lactis, S. diacetylactis, S. cremoris under controlled fermentation [75]. Buffalo milk has high total solids content (16.3 to 18.4%); protein (3.8 to 4.5%), fat (6.6 to 8.8%), lactose (4.5 to 5.2%), and casein (3.0 to 3.2%) compared with cow's milk [76] and produces a firmer curd that is a bio-therapeutic agent with a long history of use in traditional medicine.…”
Section: Dairymentioning
confidence: 99%
“…Isolating and purifying Lactobacillus strains from fifty different Meekiri samples collected from various regions in Sri Lanka reported thirty-nine different isolates, and the majority (80%) was heterofermentative lactobacilli [54]. Moreover, studying 26 Meekiri samples by Dekumpitiya et al [55], concluded that various LAB (i.e., Lactobacillus delbrueckii subsp. lactis, L. plantarum, L. helveticus, L. delbrueckii subsp.…”
Section: Indigenous Microflora In the Fermented Buffalo Milk Their Probiotic Potentials And Effect On Product Technological Propertiesmentioning
confidence: 99%
“…Today, a vast array of fermented food items and beverages is available, accounting for approximately one-third of worldwide human diets [44]. The level of probiotics in foods range from 2 to 20 g/day depending on the component and desired effect and can be added to different food products, including cereals, biscuits, bread, sauces, yogurts, and drinks [45]. Curd is considered the most preferred source of probiotics, as it is globally consumed [46].…”
Section: Probiotics and Their Benefitsmentioning
confidence: 99%